Fabrication and Characterisation of Titanium Dioxide (Tio2)/PVA Nanofibre Composites using Electrospinning - D.N. Affandi, N.; Y. Chin, L.; Fadil, F.; A. Azhar, F. (International Journal of Engineering and Technology, 2019)
A study on the formation of titanium dioxide (TiO2)/ polyvinyl alcohol (PVA) nanofibres has been investigated in the research work. In the study, the TiO2/PVA solutions were prepared at different concentrations ranging from 1wt% to 10wt%. The PVA solution without TiO2 was used as control sample in the study. Each solution was extruded using electrospinning at different voltages to form long and continuous nanofibres. The fibres were then characterised for morphological structures, fibre diameter and membrane area. The result shows that control sample of PVA nanofibres formed beads on the fibre surfaces. The addition of TiO2 in PVA was found to reduce the bead formation. The clumps of TiO2 nanoparticles were observed and were also confirmed with the EDX mapping. In addition, the electrospinning parameters affect the formation of TiO2/PVA nanofibers. At 15 kV, the resultant fibre diameter increases from 153 Â± 23 nm to 191 Â± 26 nm when the TiO2 concentration was further increased from 1wt% to 10wt%. The morphological structure of TiO2/PVA nanofibres varies depending on applied voltages and concentrations used. The membrane area of TiO2/PVA nanofibers is approximately 187 cm2 for 1wt% of TiO2. From the study, it shows that an optimalconcentration to produce TiO2/ PVA nanofibers is 10wt%. At 10wt%, no beads were observed on the fibre and the TiO2 nano-particles were uniformly distributed on the membrane surfaces.Â Â